Small molecule inhibitors for cancer immunotherapy and associated biomarkers – the current status - Schlicher, Lisa; Green, Luke G.; Romagnani, Andrea; Renner, Florian (Frontiers in Immunology, 2023)
Following the success of cancer immunotherapy using large molecules against immune checkpoint inhibitors, the concept of using small molecules to interfere with intracellular negative regulators of anti-tumor immune responses has emerged in recent years. The main targets for small molecule drugs currently include enzymes of negative feedback loops in signaling pathways of immune cells and proteins that promote immunosuppressive signals within the tumor microenvironment. In the adaptive immune system, negative regulators of T cell receptor signaling (MAP4K1, DGKα/ζ, CBL-B, PTPN2, PTPN22, SHP1), co-receptor signaling (CBL-B) and cytokine signaling (PTPN2) have been preclinically validated as promising targets and initial clinical trials with small molecule inhibitors are underway. To enhance innate anti-tumor immune responses, inhibitory immunomodulation of cGAS/STING has been in the focus, and inhibitors of ENPP1 and TREX1 have reached the clinic. In addition, immunosuppressive signals via adenosine can be counteracted by CD39 and CD73 inhibition, while suppression via intratumoral immunosuppressive prostaglandin E can be targeted by EP2/EP4 antagonists. Here, we present the status of the most promising small molecule drug candidates for cancer immunotherapy, all residing relatively early in development, and the potential of relevant biomarkers.